Research progress of circular RNA FOXO3 in diseases (review) - Min Zhao; Minting Lin; Zhibo Zhang; Linhu Ye (Global Medical Genetics)
Circular RNAs (circRNAs) are a newly discovered class of endogenous non-coding RNAs with a closed-loop structures, and they exert crucial regulatory functions in diverse biological processes and disease development through the modulation of linear RNA transcription, downstream gene expression, and protein translation, among others. Circular RNA FOXO3(circFOXO3, Hsa_circ_0006404) originates from exon 2 of the FOXO3 gene and exhibits widespread cytoplasmic expression in eukaryotic cells. It shows specific expression in different tissues or cells. Recent research has associated circFOXO3 with various diseases such as cancer, cardiovascular diseases, neurological disorders, senescence, and inflammation. However, a comprehensive review of the research progress of circFOXO3 in human diseases has not been conducted. In this paper, we provide a systematic review of the latest advances in circFOXO3 research in diseases, elucidate its biological functions and potential molecular mechanisms, and discuss the future directions and challenges in circRNAs research to provide valuable references and inspiration for research in this field.